Diagnosis company’s situation. First step towards an equality opportunity plan - Domínguez Morales, Ana (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2020)
Abstract.Royal Decree Law 6/2019 of March 1, on urgent measures to guarantee equal treatment and opportunities between women and men in employment and occupation, has amended, among others, Organic Law 3/2007, of 22 March, for the effective equality of women and men. Among other issues of great interest, Chapter III dedicated to corporate equality plans and other measures to promote equality has been modified. Within the regulation of such instruments for business management of equal opportunities between genders, we want to highligh the changes that have affected the preparation of the diagnoses prior to the implementation of equality plans. These changes were already being called for by the doctrine and could be seen in other rules of public origin aimed at promoting the development of equality plans. For example, the recommendation on the diagnosis elaboration is followed up in a negotiated manner with the employees’ representatives. In addition, the content of the report is developed by listing the subjects to be dealt in a list open. Indeed can be treated other matters in order to analysing the specific situation in the enterprise for the development of an effective equality plan.
Keywords: previous diagnosis; Equality Commission; equality plan; equal opportunities Organic Law on Gender Equity; collective bargaining